Case Report: Lennox–Gastaut Epileptic Encephalopathy Responsive to Cannabidiol Treatment Associated With a Novel de novo Mosaic SHANK1 Variant - Paprocka, Justyna; Ziętkiewicz, Szymon; Kosińska, Joanna; Kaczorowska, Ewa; Płoski, Rafał (Frontiers in Genetics, 2021)
The SHANKs (SH3 and multiple ankyrin repeat domains) are a family of scaffolding proteins located in excitatory synapses required for their development and function. Molecular defects of SHANK3 are a well-known cause of several neurodevelopmental entities, in particular autism spectrum disorders and epilepsy whereas relatively little is known about diseases associations of SHANK1. Here, we propose a novel de novo mosaic p.(Gly126Arg) SHANK1 variant as the monogenic cause of disease in a patient who presented, from the age of two years, moderate intellectual disability, autism and refractory epilepsy of the Lennox Gastaut type. The epilepsy responded remarkably well to cannabidiol (Epidiolex) add-on therapy. In-silico analyses including homology modelling and molecular dynamics simulations indicated deleterious effect of SHANK1 p.(Gly126Arg) on the protein structure and the related function associated with protein-protein interactions. In particular, the variant was predicted to disrupt a hitherto unknown conserved region of SHANK1 protein with high homology to a recently recognized functionally relevant domain in SHANK3 implicated in ligand binding, including the “non-canonical” binding of Rap1.